Interlaces between internship and extension: experiences of the extension project soils, learning and conservingby ifpe –campus Recife - Barbosa Neto, Manuella Vieira; Braga, Clezia Aquino de (Revista Ensino de Geografia (Recife), 2022)
Soil is a natural asset of great importance to humanity, however, this understanding is still incipient, and teaching and learning about soils in basic education remains a great challenge for teachers and students. The Soils, Learn and Conserveextension project, by IFPE campus Recife, started its activities in 2017, inspired by the implementation of a didactic-pedagogical intervention project of supervised internship, from the Geography Teaching course. This work aims to report the actions developed by theaforementioned extension project and demonstrate how the internship field and the experiences with the school environment have been important in this trajectory. The internship field schools became important partners in the project from the beginning, andthe undergraduates were able to contribute based on the needs that emerged from their experiences in the internship field. The experiences lived during the didactic workshops on soils contributed for the project team to develop knowledge, such as the elaboration of didactic resources more suited to each teaching modality. The extension project continues its work with the expectation of contributing to the teaching-learning process about soils in basic education schools, with the awareness that, in this joint journey of the extension project with the internship field schools, the exchange of knowledge is continuous and necessary.